A facile deposition method for CuSCN: Exploring the influence of CuSCN on J-V hysteresis in planar perovskite solar cells. (February 2017) - Sepalage, Gaveshana A.; Meyer, Steffen; Pascoe, Alexander R.; Scully, Andrew D.; Bach, Udo; Cheng, Yi-Bing; Spiccia, Leone
Abstract: Inorganic hole– transporting materials (HTMs) are a promising class of compounds for improving the long-term stability of perovskite solar cells. In this study, copper(I) thiocyanate (CuSCN) has been applied as an HTM in planar-structured thin film perovskite solar cells based on methylammonium lead(II) triiodide. A common obstacle associated with the deposition of inorganic HTMs in perovskite-based solar cell devices is the damaging effect of polar solvents, required during the solution-processed deposition step, on the underlying perovskite film. Here we describe a novel fabrication method that allows the deposition of a CuCSN layer on perovskite film, achieving a maximum power conversion efficiency of 9.6%. The magnitude of J-V hysteresis is found to be strongly dependent on the HTM used, with the phenomenon being much more prevalent in the CuSCN- and spiro-OMeTAD-based devices compared to CuI-based devices. Interestingly, CuSCN and CuI showed significantly different J-V hysteresis behaviors despite their similar physicochemical properties. Further characterization by open circuit voltage decay (OCVD) measurements revealed that the relaxation of the perovskite polarization depends on the light intensity and the adjacent HTM layer. We propose that the stronger J-V hysteresis in CuSCN compared to CuI is a result of defects generated during the deposition process and possible degradation at the material interfaces while other possibilities are also discussed. Graphical abstract: Highlights: A novel method was developed for the deposition of CuSCN. A record conversion efficiency of 9.6% was achieved . Strong hysteresis was observed in CuSCN-based devices. The impact of hole transporting material on J-V hysteresis is discussed.